2019
DOI: 10.3390/microorganisms7090344
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of mcr-1-Harboring Plasmids from Pan Drug-Resistant Escherichia coli Strains Isolated from Retail Raw Chicken in South Korea

Abstract: A number of studies from different countries have characterized mcr-1-harboring plasmids isolated from food; however, nothing has been reported about it in South Korea. In this study, we report the characterization of mcr-1 plasmids from pan drug-resistant (PDR) Escherichia coli strains isolated from retail food in the country. Colistin-resistant E. coli strains were isolated from retail raw chicken, and PCR was carried out to detect the mcr-1 gene. Whole genome sequencing of the mcr-1-positive strains was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 23 publications
(30 reference statements)
0
23
0
Order By: Relevance
“…The use of COL in humans was largely abandoned in the 1970s due to its neurotoxic and nephrotoxic effects alongside to the discovery and approval of new and effective antibiotics [ 2 ], but COL has been used in livestock for more than six decades in most countries in the world, including Africa [ 3 5 ]. In GNB, including Enterobacterales and nonfermenting GNB (such as Pseudomonas , Acinetobacter , and Aeromonas ), the major mechanism of COL resistance is by the addition of 4-amino-4-deoxy-L-arabinose (L-Ara4N) and phosphoethanolamine (pEtN) to the lipid A, a moiety of lipopolysaccharide (LPS), which decreases the electrostatic interaction between COL and LPS [ 6 , 7 ]. Before 2015, mutation in chromosomal genes, such as pmrAB , phoPQ , mgrB , and ccrB , were the known mechanisms of COL resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The use of COL in humans was largely abandoned in the 1970s due to its neurotoxic and nephrotoxic effects alongside to the discovery and approval of new and effective antibiotics [ 2 ], but COL has been used in livestock for more than six decades in most countries in the world, including Africa [ 3 5 ]. In GNB, including Enterobacterales and nonfermenting GNB (such as Pseudomonas , Acinetobacter , and Aeromonas ), the major mechanism of COL resistance is by the addition of 4-amino-4-deoxy-L-arabinose (L-Ara4N) and phosphoethanolamine (pEtN) to the lipid A, a moiety of lipopolysaccharide (LPS), which decreases the electrostatic interaction between COL and LPS [ 6 , 7 ]. Before 2015, mutation in chromosomal genes, such as pmrAB , phoPQ , mgrB , and ccrB , were the known mechanisms of COL resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, NDM-1 E. coli isolates used in this study are still susceptible to PolB in wild type cells. Meanwhile, NCCP isolates, containing the Mcr-1 expressing gene ( mcr-1 ) as a mobile element [ 35 ], showed 4-times more resistance to PolB (MIC = 3.2 μg·mL −1 ) compared to the BW25113 strain ( Table 1 ). As these isolates might have multiple resistant genes, it is difficult to see the sole Mcr-1 effect on susceptibility.…”
Section: Resultsmentioning
confidence: 99%
“…mcr-1-positive E. coli have also been found in humans and food animals in Korea [15][16][17]. However, few studies have reported mcr-1-bearing bacteria recovered from food samples in Korea [18].Since 2003, the Korean government has monitored and surveyed the antimicrobial resistance of bacteria collected from foods, such as retail meats, within the framework of the National Program on Antimicrobial Resistance Management [19]. mcr-1-positive E. coli were recently identified from retail meat samples.…”
mentioning
confidence: 99%
“…mcr-1-positive E. coli have also been found in humans and food animals in Korea [15][16][17]. However, few studies have reported mcr-1-bearing bacteria recovered from food samples in Korea [18].…”
mentioning
confidence: 99%